2003
DOI: 10.1002/jbm.a.20067
|View full text |Cite
|
Sign up to set email alerts
|

Fracture associated with hydrogen absorption of sustained tensile‐loaded titanium in acid and neutral fluoride solutions

Abstract: Abstract:The fracture of commercial pure titanium in acid and neutral fluoride solutions has been examined by a sustained tensile-loading test and hydrogen thermal desorption analysis. It was found that the fracture of titanium occurred in neutral 2.0% NaF solution as well as in 2.0% acidulated phosphate fluoride (APF) solution. The time to fracture decreased with increasing applied stress in both 2.0% APF and 2.0% NaF solutions. In the case of the same applied stress, the time to fracture in the 2.0% APF solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Fluoride contained in toothpastes and prophylactic agents has a cariostatic effect, and it has been reported that the corrosion resistance of Ni-Ti alloys is lost in fluoride solutions (Huang 2007;Lee et al 2009;Li et al 2007;Mirjalili et al 2013;Schiff et al 2002;Schiff et al 2004). Furthermore, it has been demonstrated that degradation of the mechanical properties of Ti, Ti alloys, and Ni-Ti alloys occurs in acidic and neutral fluoride solutions (Yokoyama et al 2003a;Yokoyama et al 2004a;Yokoyama et al 2004b;Kaneko et al 2003;Yokoyama et al 2005). Ni-Ti alloys absorb substantial amounts of hydrogen from acidic fluoride solutions, thereby causing hydrogen embrittlement of the alloys (Yokoyama et al 2003a;Yokoyama et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoride contained in toothpastes and prophylactic agents has a cariostatic effect, and it has been reported that the corrosion resistance of Ni-Ti alloys is lost in fluoride solutions (Huang 2007;Lee et al 2009;Li et al 2007;Mirjalili et al 2013;Schiff et al 2002;Schiff et al 2004). Furthermore, it has been demonstrated that degradation of the mechanical properties of Ti, Ti alloys, and Ni-Ti alloys occurs in acidic and neutral fluoride solutions (Yokoyama et al 2003a;Yokoyama et al 2004a;Yokoyama et al 2004b;Kaneko et al 2003;Yokoyama et al 2005). Ni-Ti alloys absorb substantial amounts of hydrogen from acidic fluoride solutions, thereby causing hydrogen embrittlement of the alloys (Yokoyama et al 2003a;Yokoyama et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…For immersion of Ni-Ti alloys in 0.2 % APF solution, the presence of diffusive hydrogen was not observed (Yokoyama et al 2003a;Yokoyama et al 2004a;Yokoyama et al 2004b). Therefore, by focusing on hydrogen that diffuses into the center of the Ni-Ti superelastic alloy, the effect of aging at room temperature on hydrogen embrittlement behavior of Ni-Ti superelastic alloy can be evaluated after immersion in 0.2 % APF solution.…”
Section: Introductionmentioning
confidence: 99%
“…A problem of using titanium alloys in the oral environment is the degradation of mechanical properties associated with the absorption of hydrogen, that is, hydrogen embrittlement, in fluoride solutions including prophylactic agents for caries prevention. [1][2][3] The amount of hydrogen absorbed by Ti-6Al-4V alloy 3) tends to be smaller than those absorbed by commercial pure titanium 2,4) and beta titanium (Ti-11.3Mo-6.6Zr-4.3Sn) alloy 1,5) upon immersion in acidulated phosphate fluoride (APF) solution for the same time. For example, in 0.2% APF solution, corresponding to the fluoride concentration of commercial toothpastes, Ti-6Al-4V alloy 3) only absorbs a small amount of hydrogen, whereas commercial pure titanium 4) and beta titanium alloy 5) absorb substantial amounts of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The type or morphology of corrosion products on the surface of titanium alloys depends on the concentration of APF solution. [1][2][3][4][5] The role that corrosion products on the surface of titanium alloys play in the hydrogen absorption and corrosion behavior may be worth considering. If a corrosion product inhibits hydrogen absorption, it will be the first such observation for titanium alloys in fluoride solutions, and such a product can be used for surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] We have recently investigated environmental conditions for the hydrogen absorption of titanium alloys in fluoride solutions. [2][3][4][5][6][7][8][9][10] In acid fluoride solutions such as prophylactic agents, titanium and its alloys absorb substantial amounts of hydrogen, thereby causing pronounced degradation of the mechanical properties or fracture of titanium and its alloys.…”
Section: Introductionmentioning
confidence: 99%